Extracellular Vesicle-Packaged miR-195-5p Sensitizes Melanoma to Targeted Therapy with Kinase Inhibitors - Santos, Nathalia L.; Bustos, Silvina O.; Reis, Patricia P. [UNESP]; Chammas, Roger; Andrade, Luciana N. S. (MDPI, 2023)
Management of advanced melanoma remains challenging, with most BRAF (B-Raf proto-oncogene, serine/threonine kinase)-mutated metastatic patients relapsing within a few months upon MAPK inhibitors treatment. Modulation of tumor-derived extracellular vesicle (EVs) cargo with enrichment of antitumoral molecules is a promising strategy to impair tumor progression and increase treatment response. Herein, we report that restored expression of miR-195-5p, down-regulated in melanoma favoring drug resistance, increases the release of EVs enriched in the tumor suppressor miRNAs, miR-195-5p, miR-152-3p, and miR-202-3p. Incorporating these EVs by bystander tumor cells resulted in decreased proliferation and viability, accompanied by a reduction in CCND1 and YAP1 mRNA levels. Upon treatment with MAPK inhibitors, miR-195 EVs significantly decreased BCL2-L1 protein levels and increased cell death ratio and treatment efficacy. Additionally, EVs exogenously loaded with miR-195-5p by electroporation reduced tumor volume in vivo and impaired engraftment and growth of xenografts implanted with melanoma cells exposed to MAPK inhibitors. Our study shows that miR-195-5p antitumoral activity can be spread to bystander cells through EVs, improving melanoma response to targeted therapy and revealing a promising EV-based strategy to increase clinical response in patients harboring BRAF mutations.
Keywords: extracellular vesicles; MAPK inhibitors; melanoma; miR-195-5p